Fundamentos teóricos en la didáctica de Terminología para la Traducción (francés-español) - Serrano Lucas, Lucía Clara (Anales de Filología Francesa, 2010)
Terminology is closely linked to specialised translation, since there is no specialised discourse without the use of terms. Thus, the translator, as a linguistic mediator, has to implement strategies to recognise the terms and translate them appropriately. This is why the study of terminology is essential for a graduate degree in Translation. However, the needs of a translator are different to those of other users of terminology, such as terminologists or specialists, so a specific pedagogical approach is required for the didactic of Translation. In this article, we intend to define this approach through a reflection on the main aspects that should be considered in designing a curriculum in Terminology for translators. This task should be developed from the point of view of the pedagogical objectives, the theoretical and practical contents and the didactic methodology.